2013
DOI: 10.1007/s11999-012-2338-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based Therapy Improves Function in Adolescents and Young Adults With Patellar Osteochondritis Dissecans

Abstract: Background Recent advances have been made in using chondrocytes and other cell-based therapy to treat cartilage defects in adults. However, it is unclear whether these advances should be extended to the adolescent and young adult-aged patients. Questions/purposes We assessed cell-based surgical therapy for patellar osteochondritis dissecans (OCD) in adolescents and young adults by (1) determining function with the International Knee Documentation Committee (IKDC) subjective and Lysholm-Gillquist scores; and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
1
57
1
Order By: Relevance
“…The fixation of loose fragments with Herbert screws [11] or resorbable pins [12] is not free from complications such as synovitis or fractures of the screws with a loose body in the joint, which leads to joint degradation [26][27][28]. Most recently, the results of autologous chondrocyte implantation which produces a cartilage similar to the hyaline cartilage was reported [29]. Macmull [30] showed that symptomatic chondromalacia patellae lesions improved with chondrocyte implantation, especially in patients who received matrix assisted chondrocyte implantation technique (MACI).…”
Section: Discussionmentioning
confidence: 99%
“…The fixation of loose fragments with Herbert screws [11] or resorbable pins [12] is not free from complications such as synovitis or fractures of the screws with a loose body in the joint, which leads to joint degradation [26][27][28]. Most recently, the results of autologous chondrocyte implantation which produces a cartilage similar to the hyaline cartilage was reported [29]. Macmull [30] showed that symptomatic chondromalacia patellae lesions improved with chondrocyte implantation, especially in patients who received matrix assisted chondrocyte implantation technique (MACI).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical implantation may be similar to ACI, with MSCs beneath a periosteal 119 or collagen 43 cover instead of cultured chondrocytes. 45 , 60 , 67 , 74 , 84 , 103 , 104 , 109 , 119 - 123 A cell-seeded construct (analogous to MACI) may be used rather than suspended cells. 11 An ideal scaffold is nontoxic, absorbable, mechanically sound, and promotes cell growth.…”
Section: Methods Of Stem Cell Transplantationmentioning
confidence: 99%
“…Cells derived from autologous bone marrow aspirates from the iliac crest have been used for treatment of focal, traumatic chondral and osteochondral defects of the femoral condyle [ 81 87 ], femoral trochlea [ 84 , 88 , 89 ], talus [ 80 , 90 , 91 ], tibial plateau [ 89 ], and patella [ 84 , 88 , 89 ]. Other studies have addressed the use of this technique in managing other defect types, such as osteochondral lesions arising from osteochondritis dissecans [ 92 , 93 ], septic arthritis [ 94 ] and unicompartmental OA [ 95 ].…”
Section: Mesenchymal Stem Cell-based Cartilage Regeneration From Bencmentioning
confidence: 99%
“…Following aspiration, MSCs were isolated and expanded within the laboratory for 2 to 3 weeks and implanted alone [ 84 , 93 ] or in association with biomaterial matrices [ 82 , 83 , 85 , 88 ]. Alternatively, in other studies, BMDCs - also described as bone marrow concentrate [ 86 , 87 ] or bone marrow aspirate concentrate [ 89 ] - were separated using centrifugation systems [ 80 , 81 , 86 , 87 , 89 91 ].…”
Section: Mesenchymal Stem Cell-based Cartilage Regeneration From Bencmentioning
confidence: 99%